Pengaruh Self Service Technology Dan Etika Bisnis Islam Terhadap Kepuasan Konsumen Mie Gacoan Pada Generasi Z Muslim Di Surabaya - Putri Dwi Hidayati (Jurnal Ilmiah Ekonomi Islam, 2025)
This research aims to analyze the impact of self-service technology and Islamic business ethics on the customer satisfaction of Mie Gacoan among Muslim Generation Z in Surabaya. The study focuses on Generation Z as tech-savvy and religiously conscious consumers. Mie Gacoan's implementation of technology-based self-service faces both positive and negative responses from consumers. Furthermore, complaints regarding product quality and service attitude raise questions about business ethics and their alignment with Sharia values. This research adopts a quantitative method with data collection procedures through questionnaires. The sample size for this study is 120 respondents, determined using a purposive sampling technique. Data analysis in this research is conducted using multiple linear regression, implemented with SPSS version 26 software. The research findings indicate that self-service technology positively and significantly influences the customer satisfaction of Mie Gacoan among Muslim Generation Z in Surabaya, and the Islamic business ethics variable also has a positive and significant impact on the customer satisfaction of Mie Gacoan among Muslim Generation Z in Surabaya.